Effect of physical and occupational therapy on delirium duration in older emergency department patients who are hospitalized. Issue 1 (6th February 2023) - Jordano, James O.; Vasilevskis, Eduard E.; Duggan, Maria C.; Welch, Sarah A.; Schnelle, John F.; Simmons, Sandra F.; Ely, E. Wesley; Han, Jin H.
Abstract: Objective: Delirium in older emergency department (ED) adults is associated with poorer long‐term physical function and cognition. We sought to evaluate if the time to and intensity of physical and/or occupational therapy (PT/OT) are associated with the duration of ED delirium into hospitalization (ED delirium duration). Methods: This is a secondary analysis of a prospective cohort study conducted from March 2012 to November 2014 at an urban, academic, tertiary care hospital. Patients aged ≥65 years presenting to the ED and who received PT/OT during their hospitalization were included. Days from enrollment to the first PT/OT session and PT/OT duration relative to hospital length of stay (PT/OT intensity) were abstracted from the medical record. ED delirium duration was defined as the duration of delirium detected in the ED using the Brief Confusion Assessment Method. Data were analyzed using a proportional odds logistic regression adjusted for multiple variables. Adjusted odds ratios (ORs) were calculated with 95% confidence intervals (95%CI). Results: The median log PT/OT intensity was 0.5% (interquartile range [IQR]: 0.3%, 0.9%) and was associated with shorter delirium duration (adjusted OR, 0.39; 95% CI, 0.21–0.73). The median time to the first PT/OT session was 2 days (IQR: 1, 3 days) and was not associated with delirium duration (adjusted OR, 1.02; 95% CI, 0.82–1.27). Conclusion: In older hospitalized adults, higher PT/OT intensity may be a useful intervention to shorten delirium duration. Time to first PT/OT session was not associated with delirium duration but was initiated a full 2 days after the ED presentation.